Thermo-mechanical analysis of wire and arc additive layer manufacturing process on large multi-layer parts - Ding, Jialuo; Colegrove, Paul A.; Mehnen, Jorn; Ganguly, Supriyo; Sequeira Almeida, Pedro M.; Wang, Fude; Williams, Stewart W. (Elsevier, 2011)
Wire and Arc Additive Layer Manufacturing (WAALM) is gaining increasing popularity as the process allows the production of large custom-made metal workpieces with high deposition rates. The high power input of the welding process, causes significant residual stress and distortion of the workpiece. This paper describes the thermo-mechanical behaviour of the multi-layer wall structure made by the WAALM process. A 3D thermo-elastic–plastic transient model and a model based on an advanced steady-state thermal analysis are employed in this study. This modelling approach shows a significant advantage with respect to the computational time. The temperature simulations and distortion predictions are verified by comparing with the experimental results from thermo- couples and laser scanners, while the residual stresses are verified with the neutron diffraction strain scanner ENGIN-X. The stress across the deposited wall is found uniform with very little influence of the preceding layers on the following layers. The stress redistributed after unclamping with a much lower value at the top of the wall than at the interface due to the bending distortion of the sampl
Keywords: Additive Layer Manufacturing Thermo-mechanical analysis Lagrangian model Eulerian model Residual stress Distortion